1990
DOI: 10.1002/j.1460-2075.1990.tb07454.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of two distinct high-affinity receptors cross-reacting with acidic and basic fibroblast growth factors.

Abstract: The fibroblast growth factor (FGF) family consists of at least seven closely related polypeptide mitogens which exert their activities by binding and activation of specific cell surface receptors. Unanswered questions have been whether there are multiple FGF receptors and what factors determine binding specificity and biological response. We report the complete cDNA cloning of two human genes previously designated flg and bek. These genes encode two similar but distinct cell surface receptors comprised of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
294
0
5

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(309 citation statements)
references
References 62 publications
10
294
0
5
Order By: Relevance
“…RPE cells express FGF receptors and respond to the mitogenic e ect of FGF-2 (Leschey et al, 1990). Among the four receptors, FGFR-1 and 2 have a high a nity for FGF-2 (Dionne et al, 1990). In contrast, FGFR-3 preferentially binds FGF-1 (Ornitz and Leder, 1992), and FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPE cells express FGF receptors and respond to the mitogenic e ect of FGF-2 (Leschey et al, 1990). Among the four receptors, FGFR-1 and 2 have a high a nity for FGF-2 (Dionne et al, 1990). In contrast, FGFR-3 preferentially binds FGF-1 (Ornitz and Leder, 1992), and FGFR-4 binds FGF-1 with high a nity but shows low a nity for FGF-2 (Vainikka et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of FGF receptors indicated that such cells overexpress ®broblast growth factor receptor-1 (FGFR-1). Most probably, FGFR-1, which is a high a nity receptor for FGF-2 (Dionne et al, 1990), mediates the transforming e ect induced by this growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…The FGFs elicit their biological responses through high a nity binding and activation of a family of receptor tyrosine kinases, the ®broblast growth factor receptors (FGFRs). Four members of structurally related FGFRs (FGFR1/Flg, FGFR2/Bek, FGFR3 and FGFR4) have been characterized (Dionne et al, 1990;Miki et al, 1991;Keegan et al, 1991;Partanen et al, 1991;Ron et al, 1993). Extracelluarly, the receptors are composed of two or three immunoglobulin (Ig)-like domains which mediate ligand binding and interaction with heparin proteoglycans Gao and Goldfarb, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The pFlg expression vector contains the entire cDNA coding sequence for the human FGFR1 receptor (Dionne et al, 1990). We have generated a mutant termed pDFlg by deleting the region encompassing the whole tyrosine kinase domain of the transmembrane receptor.…”
Section: Plasmidsmentioning
confidence: 99%